Correlation of Mass Potatoes Fraction to Oil Volume Ratio to Physical and Chemical Oil Deterioration during Vacuum Frying - Yuniarto, Kurniawan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
The changes of some physical and chemical characteristics of edible oil used for frying of sliced potato under vacuum were studied. Three respective ratios of potato mass and the oil volume were tested, namely 1:21 (w/v), 1:32 (w/v) and Â 1:64 (w/v), and the frying process at each batch was carried out at 90 oC for a certain period of time. Frying process was performed in 24 hours daily, in which the oil was used repeatedly. In 5 minutes interval, the temperature of the oil and the pressure level of the frying vessel were recorded. The samples of oil was randomly taken from the frying batches to determine any changes in the free fatty acid content and peroxide number (chemical aspects), and the physical characteristics (color and viscosity). Â Based on the set values of the parameters, the maximum time for oil usage on frying was estimated by employing a mathematical model and then compared with empirical data. The results showed that the maximum time for oil usage, at which the oil volume was no longer enough for deep frying, was reduced with increasing the potato mass. It was partly due to the longer retention time for frying of the higher potato mass. The change rate observed for free fatty acid was 0,0016 unit/hr, while the one for the peroxide number was undetected. The change rates for the color and viscosity were 0,03 unit/hr and 0,55 unit/hr respectively. The highest rate of changes on the free fatty acid and viscosity were found on the ratio of 1:21. Based on the empirical data, the oil may be used for frying up to 80 hrs, compared to only 62 hrs with the mathematical model.Keywords : vacuum frying, potato, oil deterioration, mass potatoes fraction to oil volume ratio